2020
DOI: 10.1111/beer.12288
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sector alliances in the global refugee crisis: An institutional theory approach

Abstract: The global refugee crisis has posed severe challenges to social stability and sustainable development around the world. While the business sector is expected to shoulder social responsibility in crisis relief efforts, our initial assessment shows that refugee‐related corporate social responsibility (CSR) significantly diverged across the Global Fortune 500 corporations. To advance scholars and managers' understanding of this complex CSR issue, this study draws upon National Business System Theory to explore ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 71 publications
(93 reference statements)
2
21
1
Order By: Relevance
“…Most companies accordingly marginalise controversies and criticism. Stakeholder alliances (Baranova & Meadows, 2017; Yang, Liu, & Wang, 2020) and the United Nations Global Compact (Arevalo, Aravind, Ayuso, & Roca, 2013) serve the same harmonising purpose. When companies enter these alliances it helps to give the impression of harmony rather than a conflict of interest between profit‐oriented companies and non‐profit organisations.…”
Section: Justification Fallaciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most companies accordingly marginalise controversies and criticism. Stakeholder alliances (Baranova & Meadows, 2017; Yang, Liu, & Wang, 2020) and the United Nations Global Compact (Arevalo, Aravind, Ayuso, & Roca, 2013) serve the same harmonising purpose. When companies enter these alliances it helps to give the impression of harmony rather than a conflict of interest between profit‐oriented companies and non‐profit organisations.…”
Section: Justification Fallaciesmentioning
confidence: 99%
“…Most companies accordingly marginalise controversies and criticism. Stakeholder alliances (Baranova & Meadows, 2017;Yang, Liu, & Wang, 2020) and the United Nations Global Compact (Arevalo, Aravind, Ayuso, & Roca, 2013) serve the same harmonising purpose.…”
Section: Conflict Avoidancementioning
confidence: 99%
“…This model can not only detect the outbreak of sudden disaster events but also output the outbreak time and affected area of the disaster quickly, which could be in favor of the following data collection and update. The Leshan Earthquake case research confirmed that the output of the above model could effectively serve the real-time and intelligent collection of disaster microblog information in the affected disaster area, which is conducive to providing a useful real-time data source for dynamic emergency response [Yang, A., 2020].…”
Section: Introductionmentioning
confidence: 82%
“…We used companies' industry information provided by Fortune for further classi cation. Consulting the Standard Industrial Classi cation (SIC) and Industry Classi cation Benchmark (ICB), both widely used by scholars and nancial sectors for categorization (e.g., NYSE, NASDAQ, Arun et al, 2015;Yang et al, 2020), we classi ed the 2018 Fortune Global 500 companies into three categories: traditional ( = 62), services ( = 140), and high tech ( = 34), similar to Zéghal and Maaloul (2010). The detailed classi cation scheme can be found in Table 1 of the online Appendix.…”
Section: Data Labelingmentioning
confidence: 99%